ANALISIS PANGSA PASAR DAN DAYA SAING CPO INDONESIA DI UNI EROPA - Dian Widyaningtyas; Tri Widodo (Jurnal Manajemen Dayasaing, 2016)
Commodities of palm oil play a strategic role in the Indonesia’s economy. In this study we concern on the competitiveness of Indonesia’s Crude Palm Oil (CPO) industry and effectiveness of the potential market for Indonesia’s CPO in Uni Europe (UE). The utilization of CPO as biofuels, encouraging an significant increased of demand for CPO in UE. This study is also addressed to determine the Indonesian CPO performance among other palm oil producer country. We used the revealed comparative advantage (RCA) and market share index (MSI) methods in analysing the competitiveness level. Our results showed, in 2014, export performance of Indonesia’s CPO increased. It was showed by the value of RCA1. Indonesia has competitiveness of CPO, because of the increased export volume of CPO and it’s derivates product to the major importer countries, such as UE. However, the average of RCA analysis in 2007-2014 indicate the lower performanceof Indonesia’s CPO exports compared to the other main CPO exporter, Malaysia. Thus, from the MSI analysis we found that Italy is a potential market for Indonesia’s palm oil exports, based on the fact that Indonesia’s CPO dominated the Italian market in the last seven years. The value of Indonesia’s market share was far above the competitor.